2014
DOI: 10.1097/igc.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Circumflex Iliac Node Distal to the External Iliac Node Metastasis in Stage IA to IIA Cervical Carcinoma

Abstract: Circumflex iliac node distal to the external iliac node metastases seemed to occur secondarily to widespread PLN metastases. In early stage cervical cancer, removal of the CINDEIN as a routine surgical procedure might be omitted to reduce operation time and minimize surgical morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For cervical cancer patients, lymph nodes status is a critical predictor of survival that has been applied to guide clinical treatment ( 16 ). The risk of lymph node metastasis increases per FIGO stage (2009 version), with incidences from 2% (stage IA2) to 14–36% (IB), 38–51% (IIA), and 47% (IIB) in the pelvic region; and from 2% to 5% (stage IB), 10–20% (IIA), 9% (IIB), 13–30% (III), and 50% (IV) in the paraaortic region ( 17 , 18 ). Once cervical cancer with lymph node metastasis occurs, the survival rate of patients is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…For cervical cancer patients, lymph nodes status is a critical predictor of survival that has been applied to guide clinical treatment ( 16 ). The risk of lymph node metastasis increases per FIGO stage (2009 version), with incidences from 2% (stage IA2) to 14–36% (IB), 38–51% (IIA), and 47% (IIB) in the pelvic region; and from 2% to 5% (stage IB), 10–20% (IIA), 9% (IIB), 13–30% (III), and 50% (IV) in the paraaortic region ( 17 , 18 ). Once cervical cancer with lymph node metastasis occurs, the survival rate of patients is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This group of lymph nodes is usually included in CTV in previous studies [ 32 , 33 ], but seldom mentioned with specific contouring recommendations. Several reports, including our previous study [ 29 , 31 , 34 ], have described the incidence of the CINDEIN metastasis in cervical cancer from 2.5% to 8% and have demonstrated that CINDEIN is seldom involved in metastasis. In the present study, we found that 17 of 665 patients had CINDEIN involvement and the incidence of CINDEIN metastases was 2.6%.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the metastatic rate of CINDEIN is low. Previous studies showed that the percentage of CINDEIN metastasis was 0% to 2.6% in patients with FIGO stage up to IIb [ 16 17 ], and 4.0% to 10.1% in patients with pN1 disease [ 5 7 17 ]. In our study, the percentage of CINDEIN metastasis was 1.9% in all patients and 3.4% in patients who underwent removal of CINDEIN.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety percent of patients with CINDEIN metastasis had multiple lymph node metastases and 80% had positive parametrial involvement. Yin et al [ 17 ] showed that CINDEIN metastases were strongly correlated with metastases of the obturator, external iliac, and IIN [ 17 ]. They found that 94% of patients with CINDEIN metastasis were associated with multiple sites of pelvic lymph node metastases, which was compatible with our results.…”
Section: Discussionmentioning
confidence: 99%